1975
DOI: 10.1111/j.1532-5415.1975.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacologic Investigations in Healthy Elderly Volunteers: Effects of Pipradrol‐Vitamin (Alertonic) Elixir and Placebo in Relation to Research Design†

Abstract: Ninety-nine healthy elderly volunteers were tested to assess the effects of: 1) a pipradrol-vitamin (Alertonic) elixir, 2) a placebo, and 3) no treatment, during a one-week period. The assessment measures were the Minnesota Multiphasic Personality Inventory Depression Scale, the Zung Depression Scale, Profile of Mood States, and the WAIS Digit Span. Alertonic had no sigmificant effects on mood, memory or appetite, and the placebo effect was rarely greater than 50 per cent. There were no significant side eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Other tests, which gain their discriminating ability from graduated responses to more socially neutral items like appetite problems, are more likely to show the older respondents scoring higher than the young ones (16). Our own experience (1) supports the usefulness of the Zung self‐rated Depression Scale for purposes of preliminary screening. Similarly, our attempts to evaluate treatment‐induced short‐term affective states have shown that elderly people are much more comfortable using lists like the Depression Adjective Check List (17) than when using MMPI‐derived measures.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Other tests, which gain their discriminating ability from graduated responses to more socially neutral items like appetite problems, are more likely to show the older respondents scoring higher than the young ones (16). Our own experience (1) supports the usefulness of the Zung self‐rated Depression Scale for purposes of preliminary screening. Similarly, our attempts to evaluate treatment‐induced short‐term affective states have shown that elderly people are much more comfortable using lists like the Depression Adjective Check List (17) than when using MMPI‐derived measures.…”
Section: Discussionsupporting
confidence: 52%
“…Recently the Psychopharmacology Research Laboratory (PRL) at Harvard Medical School began a series of investigations into the emotional effects of psychotropic drugs taken by elderly persons (1). In parallel work with younger volunteers, the importance of preliminary screening has been stressed; the screening methods included personality trait measures of anxiety and depression (2–4).…”
mentioning
confidence: 99%
“…The Zung scale was chosen because of the extensive work done with it in the area of geriatric depression 12 and because of reports attesting to its sensitivity to mild changes in affect in elderly patients. 13 These procedures were also administered by clinic staff members at the time of the neuropsychological assessment.…”
Section: Behavioral Assessmentmentioning
confidence: 99%
“…We studied a combination product containing pipradrol and vitamins. 8,9 We found the product to be ineffective. From my background reading for this Note, I was surprised to learn that pipradrol is listed as a Class A-prohibited drug for Olympic athletes.…”
Section: When Is a Signal A True Signal? Pemoline As A Confusing Casementioning
confidence: 82%